Euthanasia in Wildlife Rehabilitation and Specific Considerations for Pelagic and Diving Bird Rehabilitation - Bill, January (Wildlife Rehabilitation Bulletin, 2005)
It is the goal and responsibility of wildlife rehabilitators to provide the best achievable care to the animals that are brought to them for help. Because of the nature of wildlife rehabilitation, by the time the rehabilitator receives the animal, its injuries and/or illness have often progressed to a state beyond a point that will enable the animal to survive when returned to the wild. If an animal cannot be returned to a normal life in the wild, the only options rehabilitators have for a non–releasable animal in their care is life in captivity or euthanasia (Miller 1993). Just as it is vital to have the skills and knowledge to successfully treat a species of wildlife, it is equally important to have the skills to evaluate the animal for euthanasia on intake. Euthanasia is often the only viable option to humanely end an animal’s pain and prevent further suffering. Therefore, euthanasia decisions based on physiological evidence and well–reasoned judgment lead to more humane treatment of wildlife in rehabilitation. The objective of this paper is to emphasize the importance of this aspect of wildlife rehabilitation, to provide basic euthanasia guidelines, and to outline a set of specific considerations for pelagic and diving bird rehabilitation used at International Bird Rescue Research Center (IBRRC).